Praktik Wali Muhakkam di Desa Lhok Medang Ara Kecamatan Manyak Payed Kabupaten Aceh Tamiang Menurut Fiqh Munakahat - Rahmad Fauzi; Faisar Ananda Arfa (Departement of Mathematics Education, 2023)
Article 23 paragraphs (1) and (2) of the KHI state that the new judge's guardian can act as marriage guardian if the nasab guardian is not available or is unable to present him or his place of residence is unknown or is unseen, adhal or reluctant. This marriage with the muhakkam guardian occurred because the prospective husband and wife were not married to the nasab guardian, they were reluctant to deal with the judge's guardian because they wanted to take the easy route in getting married. The research method in this research is empirical legal research, because the information and data needed are extracted and collected from the field which is descriptive in nature. This research includes field research, while the research location is in Manyak Payed District, Aceh Tamiang Regency. In addition to observations, this research also uses the interview method with Community Leaders and Marriage Practitioners using Based on the analysis presented by the author, several conclusions can be drawn as follows: 1. The practice of marriage with muhakkam guardians is carried out by married couples whose guardians are adhol (reluctant) , supposedly if the guardian is adhol (reluctant) or does not have a nasab guardian then the one who has the right to marry them is the judge's guardian. This marriage is invalid. Likewise, according to positive law, a marriage is not valid if it is not recorded and registered at the Office of Religious Affairs (KUA). This will create ambiguity regarding their marital status because they do not have a marriage certificate. 2. Fiqh Munakahat's review of the case above violates the rules of Islamic law. Marriage using a muhakkam guardian in modern times is not valid because almost every sub-district always has a Religious Affairs Office (KUA) which has been authorized to marry someone who does not have a guardian . The action taken by a husband and wife by appointing a muhakkam guardian in their marriage is an action outside the provisions of Islamic law.